2022
DOI: 10.1101/2022.05.14.22275077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implication of Hepsin from primary tumor in the prognosis of colorectal cancer patients

Abstract: BackgroundHepsin is a type II transmembrane serine protease whose functions include degradation of the extracellular matrix and activation of factor VII. In many tumors, hepsin dysregulation leads to tumor invasion by proteolysis of pericellular components. Colorectal cancer is a tumor with high thrombotic and metastatic risk, but the role of hepsin is unknown.ObjectivesTo study the correlations between hepsin expression in the primary tumor and different clinical-histopathological variables in patients with l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 47 publications
2
7
1
Order By: Relevance
“…Instead, hepsin activity is regulated downstream via a Ras pathwaydependent mechanism [7]. However, in our recently published study, we found no association between Ras mutation and hepsin levels [13].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Instead, hepsin activity is regulated downstream via a Ras pathwaydependent mechanism [7]. However, in our recently published study, we found no association between Ras mutation and hepsin levels [13].…”
Section: Discussioncontrasting
confidence: 69%
“…In fact, thromboembolic disease is often associated with metastasis [46]. Hepsin overexpression of our cell line clearly increased procoagulant phenotype as we observed in localized CRC patients [13]. These observations led us to hypothesize that some TTSPs, including hepsin, contribute to hypercoagulability in vivo by generating thrombin in the phase boundary of the tumor invasion and migration front, together with other mediators [49,50].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations